2021
DOI: 10.1007/s13178-021-00676-6
|View full text |Cite
|
Sign up to set email alerts
|

Racialized Sexual Discrimination (RSD) and Psychological Wellbeing among Young Sexual Minority Black Men (YSMBM) Who Seek Intimate Partners Online

Abstract: Introduction Online dating is widespread among young adults, and particularly young sexual minority men. Racialized sexual discrimination (RSD), also known as “sexual racism,” is frequently reported to occur within these digital spaces and may negatively impact the psychological wellbeing of young sexual minority Black men (YSMBM). However, the association between RSD and psychological wellbeing is not well understood. Methods Using data (collected between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…Contrary to predictions, we found no differences on White physical objectification, same-race rejection, or role assumptions frequencies based on primary venue. previous research, in which we found that same-race rejection was significantly associate with higher self-reported depressive symptomatology among YSMBM [45]. In this sam study, we found that White superiority was also associated with higher scores on depre sive symptoms, and our current study findings indicate that White superiority is encou tered much more frequently on Grindr compared with Jack'd.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Contrary to predictions, we found no differences on White physical objectification, same-race rejection, or role assumptions frequencies based on primary venue. previous research, in which we found that same-race rejection was significantly associate with higher self-reported depressive symptomatology among YSMBM [45]. In this sam study, we found that White superiority was also associated with higher scores on depre sive symptoms, and our current study findings indicate that White superiority is encou tered much more frequently on Grindr compared with Jack'd.…”
Section: Discussionsupporting
confidence: 71%
“…If rejection from other Black users does not occur significantly more frequently on Jack’d than on Grindr, in spite of the purportedly higher number of Black users on Jack’d, this may indicate that YSMBM are more sought after on Jack’d in relative terms, based on the sociodemographic differences of these two dating environments. This may be particularly important in light of our previous research, in which we found that same-race rejection was significantly associated with higher self-reported depressive symptomatology among YSMBM [ 45 ]. In this same study, we found that White superiority was also associated with higher scores on depressive symptoms, and our current study findings indicate that White superiority is encountered much more frequently on Grindr compared with Jack’d.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…All study covariates performed identically to previous main effects analyses examining the relationship between RSD and psychological well-being. We discuss the implications of these associations at length in prior published work [ 31 ]. In addition, all three RSD subscales were associated with poorer psychological well-being ( H1 ), consistent with our prior work, as well as other scholars’ work examining sexual racism among sexual minority men of color [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have demonstrated links between RSD and negative health outcomes, such as anxiety and psychological distress—as well as lower self-esteem and well-being among sexual minority men of color [ 24 , 25 , 26 , 27 , 28 , 29 ]. In a series of recent studies, we developed the first psychometrically evaluated scale of RSD and examined the association between RSD and psychological well-being among young sexual minority Black men (YSMBM) [ 30 , 31 ]. We found that encountering same-race rejection and White superiority when seeking intimate partners online was associated with higher depressive symptoms among YSMBM.…”
Section: Introductionmentioning
confidence: 99%